Survival and growth characteristics of forest pine plantations established with different planting stock types in the south-eastern part of the Left-Bank Forest-Steppe of Ukraine - Ющик, В. С. (Forestry and Forest Melioration, 2024)
Introduction The planting of forest stands remains predominant among the various methods of restoring pine forests in the country. In the Kharkiv region, no recent research has been conducted on the growth characteristics of Scots pine plantations established using different planting technologies and planting stock types. This gap in research highlights the relevance of the present study. The aim of this research was to evaluate the growth and survival rates of two- and three-year-old Scots pine plantations established using different planting methods and planting stock types in fresh infertile and fresh relatively infertile pine site types. The goal was to determine the optimal technology for establishing pine stands in the south-eastern part of the Left-Bank Forest-Steppe of Ukraine. Materials and Methods The study was conducted at the Branch “Zhovtneve Forestry” of the State Specialized Forest Enterprise “Forests of Ukraine” (Merefianske forest district) and Kharkiv Forest Research Station (Derhachivske and Lypetske forest districts) in fresh infertile pine site types and fresh relatively infertile pine site types. Measurements and assessments of growth indicators – height, height increment, root collar diameter – and survivability- were performed on two- and three-year-old Scots pine plantations established using different planting methods, planting stock types, and stand compositions. The survivability in the second and third years of cultivation was determined as the ratio of the number of viable plants at the time of assessment to the initial number of planting spots, expressed as a percentage. The collected data were analysed using mathematical statistics in MS Excel. The significance of the difference between control and experimental variants was tested using Student's t-test at a 5% significance level. Results Two-year-old plantations in the Merefianske forest district. It was found that pure plantations in fresh relatively infertile pine site types established by hand planting exhibited higher growth rates compared to pure plantations established by mechanised planting, mixed plantations, and pure plantations in fresh infertile pine site types. This differences in growth parameters were as follows: height – 1%, 4%, and 12%; height increment – 4%, 5%, and 8%; and root collar diameter –7%, 9%, and 16%, respectively. The highest survival rate was recorded for pure plantations in fresh relatively infertile pine site types established by hand planting, while the lowest (80%) was observed in plantations in fresh infertile pine site types established by hand planting. Three-year-old plantations in Merefianske forest district. The results showed that pure plantations in fresh relatively infertile pine site types established by hand planting exhibited higher growth rates compared to pure plantations established by mechanised planting, mixed plantations, and pure plantations in fresh infertile pine site types. This differences in growth parameters were as follows: height—4%, 3%, and 10%; height increment—6%, 8%, and 15%; and root collar diameter—4%, 6%, and 11%, respectively. The highest survival rate (80%) was recorded in pure plantations in fresh relatively infertile pine site types established by hand planting, while the lowest (77%) was observed in plantations in fresh infertile pine site types established by hand planting. Two-year-old plantations in Derhachivske forest district. The research results indicate that plantations in fresh relatively infertile pine site types established using containerised seedlings exhibited higher growth rates compared to those planted with bare-root seedlings. The differences observed were 13% in height and 15% in both height increment and root collar diameter. Additionally, plantations established with containerised seedlings demonstrated a higher survivability (88%) compared to those planted with bare-root seedlings (82%). Three-year-old plantations in Lypetske forest district. The research results show that plantations in fresh fairly infertile pine site types established with containerised seedlings exhibited superior growth rates compared to those planted with bare-root seedlings. The differences recorded were 28% in height, 21% in height increment, and 16% in root collar diameter. Plantations established with containerised seedlings also exhibited higher survivability (85%) compared to those planted with bare-root seedlings (80%). Conclusions To enhance the technology of pine plantation establishment in the study region, the broader use of containerised planting stock is recommended for pine forest restoration. Additionally, expanding the proportion of mixed plantations, particularly those established using mechanised method, is advised. 5 Tables, 18 Refs.